Identification of contact residues in the IgE binding site of human FcepsilonRIalpha. - Cook, J; Henry, A; McDonnell, J; Owens, R; Sutton, B; Gould, H (1997)
The high-affinity receptor for immunoglobulin E (IgE), FcepsilonRI, is an alphabetagamma2 tetramer found on mast cells, basophils, and several other types of immune effector cells. The interaction of IgE with the alpha-subunit of FcepsilonRI is central to the pathogenesis of allergy. Detailed knowledge of the mode of interaction of FcepsilonRI with IgE may facilitate the development of inhibitors for general use in the treatment of allergic disease. To this end we have performed site-directed mutagenesis on a soluble form of the FcepsilonRI alpha-chain (sFcepsilonRIalpha). The effects of four mutations in the second immunoglobulin-like domain of sFcepsilonRIalpha upon the kinetics of binding to IgE and fragments of IgE have been analyzed using surface plasmon resonance. As described in the preceding paper of this issue [Henry, A. J., et al. (1997) Biochemistry 36, 15568-15578], biphasic binding kinetics was observed. Two of the mutations had significant effects on binding: K117D reduced the affinity of sFcepsilonRIalpha for IgE by a factor of 30, while D159K increased the affinity for IgE by a factor of 7, both principally through changes in the rates of dissociation of the slower phase of the interaction. Circular dichroism spectra of sFcepsilonRIalpha incorporating either of these mutations were indistinguishable from those of wild-type sFcepsilonRIalpha, demonstrating that the native conformation had not been disrupted. Our results, together with those from site-directed mutagenesis on fragments of IgE presented in the accompanying paper, define the contact surfaces in the IgE:sFcepsilonRIalpha complex.